Core Concepts in Acute Kidney Injury (Springer US, 2018)
This comprehensive guide covers the causes, characteristics, and presentations of acute kidney injury (AKI), as well as prevention and treatment. The first part of the book features chapters on the epidemiology and diagnosis of AKI. This is followed by sections on pathophysiology, clinical syndromes and patient management. Authored by leading clinicians, epidemiologists, basic scientists, and clinical trialists, this book captures the latest evidence and best practices for treating patients with AKI.